Equivalent modeling for a finite element analysis of the mechanical properties of a bolted joint with a superelastic shape memory alloy. (March 2023) - Dong, Xingkun; Jiang, Xiangjun; Wang, Yanping; Li, Peng; Pan, Fengqun
In this study, a beam element model with tension–compression asymmetry is constructed by using the improved Brinson model. A comparison between the calculated and experimental results verifies the computational effectiveness of the beam element. Then, a new mechanical property analysis model of a shape memory alloy (SMA) bolted joint based on the beam element model is proposed. Combined with a constructed convergence function, the mechanical equilibrium state of the SMA bolted joint under preload and external load is solved iteratively by the bisection method. Consequently, the stress–strain response curve of the SMA bolt rod and the root of the first thread, the deformation law of each thread and the separation conditions of the contact surface of members are analyzed by the proposed model. It is shown that the new proposed method can greatly improve the calculation efficiency with high calculation precision compared with the traditional calculation method.